2018
DOI: 10.1177/1362361318782220
|View full text |Cite
|
Sign up to set email alerts
|

Mothers of children with autism spectrum disorders: Play behaviors with infant siblings and social responsiveness

Abstract: Mother-infant interactions are a proximal process in early development and may be especially salient for children who are at risk for social difficulties (i.e. infant siblings of children with autism spectrum disorder). To inform how indices of maternal behaviors may improve parent-mediated interventions designed to mitigate autism spectrum disorder risk, the present study explored maternal social responsiveness ratings and social behaviors during dyadic play interactions. Dyads were recruited from families wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…There are several methodological considerations related to measuring caregiver speech and infant language development that warrant discussion. The majority of infant autism studies of parent–child interactions measure caregiver speech and infant vocalizations from short, 10–13 min videos (Campbell et al, 2015; Chericoni et al, 2016; Heymann et al, 2018; Ozonoff et al, 2010; Schwichtenberg, Kellerman, Young, Miller, & Ozonoff, 2018; Walton & Ingersoll, 2015). Short video recordings produce a different account of the language heard by a child when compared to day-long audio recordings collected in the home (Bergelson, Amatuni, Dailey, Koorathota, & Tor, 2018).…”
Section: Methodological Considerations Related To Measuring Infant Lamentioning
confidence: 99%
“…There are several methodological considerations related to measuring caregiver speech and infant language development that warrant discussion. The majority of infant autism studies of parent–child interactions measure caregiver speech and infant vocalizations from short, 10–13 min videos (Campbell et al, 2015; Chericoni et al, 2016; Heymann et al, 2018; Ozonoff et al, 2010; Schwichtenberg, Kellerman, Young, Miller, & Ozonoff, 2018; Walton & Ingersoll, 2015). Short video recordings produce a different account of the language heard by a child when compared to day-long audio recordings collected in the home (Bergelson, Amatuni, Dailey, Koorathota, & Tor, 2018).…”
Section: Methodological Considerations Related To Measuring Infant Lamentioning
confidence: 99%
“…Conversely, Yirmiya et al [2006] reported no difference in instances of infant‐led, mother‐led, mutual synchrony, or response time between dyads in high‐ vs. low‐risk groups. Similarly, several studies in the first year have reported no significant high‐ or low‐risk group differences in infant or mother vocalizations, positive affect, use of multimodal bids [Schwichtenberg et al, 2019], parent initiating/directing, praise, scaffolding, warmth, sensitivity [Campbell, Leezenbaum, Mahoney, Moore, & Brownell, 2016], responsiveness [Leezenbaum et al, 2014], or time engaged during play [Steiner et al, 2018]. Alternatively, some studies document mothers in the high‐risk group as more synchronous [Steiner et al, 2018] and including more gestures [Talbott et al, 2016], when compared to a low‐risk group.…”
Section: Familial Asd Risk Group Comparisonsmentioning
confidence: 96%
“…Similarly, Kellerman et al [2019] documented subclinical dyadic features of ASD evident during play by 15 months of age (i.e., lower infant and maternal responsiveness; lower joint engagement). However, several studies have demonstrated that parents of children with ASD are comparable interactive partners, when compared to parents of children with typical development and those with other developmental concerns [Kasari, Sigman, Mundy, & Yirmiya, 1988;Schwichtenberg et al, 2019;Siller & Sigman, 2002]. Notably, many studies go beyond group-based outcome assessments (e.g., ASD vs. Not ASD) to consider continuous measures of developmental competence.…”
Section: Developmental Progress/outcome Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Video depicted infants and parents playing together with age‐appropriate toys. Segments were selected from a task that used a standardized toy set and instructed parents to play with their child as they would at home (Schwichtenberg, Kellerman, Miller, Young, & Ozonoff, ). Video recordings utilized a consistent camera angle facing the child, with the parent in profile.…”
Section: Methodsmentioning
confidence: 99%